Antimicrobial activities of sesquiterpene lactones and inositol derivatives from Hymenoxys robusta - Fortuna, Antonio Mario (2011)
Six compounds from the aerial parts of the Argentinean plant Hymenoxys robusta (Rusby) Parker were isolated and their structures elucidated using extensive spectroscopic analyses. These compounds comprise two inositol derivatives and four 3,4-seco-pseudoguaianolides, including vermeerin. Bioactivity assays of these compounds against bacterial and fungal pathogens showed that only vermeerin possessed antimicrobial activity specific against Staphylococcus aureus, and showed no toxicity when exposed to human-derived macrophages.